Position and Resistance in Abdullah Pashew's Poems - البرزنجي, ا.م.د. عثمان عبد المعروف البرزنجي (Sulaimani Journal for Humanities, 2025)
The essence of freedom and prosperity within a nation hinges upon the unity and consciousness of its people. This necessitates literature that reflects the nation's reality and serves as a catalyst for societal awakening. Particularly, revolutionary and resistance literature plays a pivotal role in galvanizing poets and intellectuals to confront invaders and injustices, thereby inspiring society to struggle and defend itself. This research, titled “Resistance in Abdullah Pashew's Poems," is structured into two primary sections: Part One delves into Pashew's life and works, while Part Two examines how resistance is portrayed in his poetry. Employing scientific research methods, including descriptive analysis, social criticism, and at times historical approaches, our research aims to illuminate the thematic underpinnings of Pashew's poetry.
Keywords: Attitude; resistance; alienation; social criticism; scientism